Aurat dan Penegakan Syariat: Tinjauan Fiqih Syafi’i terhadap Qanun Jinayat Aceh - Muhajir Muhajir; Yustizar Yustizar (Legalite : Jurnal Perundang Undangan dan Hukum Pidana Islam, 2026)
This study aims to analyze the legal construction of aurat within the perspective of Shafi‘i fiqh and its relevance to the implementation of Qanun Aceh Number 6 of 2014 on Jinayat Law in the enforcement of Islamic law in Aceh. This research is categorized as field research employing a qualitative approach and a socio-juridical method. Primary data were obtained through in-depth interviews with religious scholars, Wilayatul Hisbah officers, sports coaches, Muslim athletes, and members of the public in North Aceh, East Aceh, and Langsa City. Secondary data were derived from Shafi‘i fiqh literature, sharia regulations, scholarly journals, and relevant legal documents. Data were analyzed descriptively and analytically through data reduction, categorization, and triangulation of normative and empirical findings. The study reveals that the implementation of aurat regulations in Aceh has shifted from an ethical-religious norm into an instrument of public moral control exercised by the state. The enforcement of sharia demonstrates tensions between Shafi‘i fiqh doctrines, state interpretation, and the social realities of contemporary Acehnese society. The enforcement practices tend to be symbolic and repressive, generating issues related to social legitimacy, gender relations, and the limits of state authority within the public sphere of Muslim society in Aceh.